Blended or Hybrid Learning and Written Understanding of English in Higher Education (Docentes 2.0 Journal, 2025)
Blended learning integrates in-person and virtual components, promoting a dynamic environment tailored to students' needs. This model favors the development of language skills through videoconferencing, multimedia materials, and interactive methodologies. Written comprehension is key to English language acquisition, as it involves interpreting, connecting, and applying written information, with lexical knowledge being a key factor. This study aimed to analyze the impact of blended learning on English written comprehension in higher education. The research was conducted within the positivist paradigm, using a systematic method, a quantitative approach, a narrative-thematic design, a documentary-bibliographic approach, and a longitudinal section. Twenty-seven articles from databases such as Scopus and Web of Science were analyzed, evaluating methodologies and results in English- and Spanish-speaking contexts. The findings indicate that blended learning improves written comprehension by offering motivating and effective experiences. Blended learning models, such as blended learning, have demonstrated a positive impact on the development of language skills. Furthermore, they allow personalized teaching and optimized interaction between teachers and students, even in challenging contexts such as the COVID-19 pandemic. The findings highlight the relevance of hybrid learning in English language teaching and suggest its integration into future pedagogical strategies.
Keywords: Blended learning; written comprehension; higher education; English language teaching